How to evaluate the impact of corporate purpose - Busch, Christian (Professor of business); Hehenberger, Lisa (MIT Sloan Management Review, 2022)
Corporate purpose will deliver on the promise of a more engaged workforce and more loyal customers only if companies develop the capacity to accurately assess the results of executing their purpose-driven strategy, particularly its social and environmental impact. To accomplish that, they must first understand the organization's current impact and shift thinking about ESG performance indicators from tracking inputs to showing evidence of results.